Effects of Prenatal Exposure to Titanium Dioxide Nanoparticles on DNA Methylation and Gene Expression Profile in the Mouse Brain - Tachibana, Ken; Kawazoe, Shotaro; Onoda, Atsuto; Umezawa, Masakazu; Takeda, Ken (Frontiers in Toxicology, 2021)
Background and Objectives: Titanium dioxide nanoparticles (TiO2-NP) are important materials used in commercial practice. Reportedly, TiO2-NP exposure during pregnancy can affect the development of the central nervous system in mouse offspring; however, the underlying mechanism remains unknown. In the present study, we investigated the impact of prenatal TiO2-NP exposure on global DNA methylation and mRNA expression patterns in the brains of neonatal mice. Materials and Methods: Pregnant C57BL/6J mice were intratracheally administered a TiO2-NP suspension (100 μg/mouse) on gestational day 10.5, and brains were collected from male and female offspring at day 1 postpartum. After extraction of methylated DNA by immunoprecipitation, the DNA methylation profile was analyzed using a mouse CpG island microarray. Total RNA was obtained, and mRNA expression profiles were comprehensively assessed using microarray analysis. Results: Among genes in the CpG island microarray, DNA methylation was increased in 614 and 2924 genes and decreased in 6219 and 6463 genes in male and female offspring, respectively. Combined with mRNA microarray analysis, 88 and 89 genes were upregulated (≥ 1.5-fold) accompanied by demethylation of CpG islands, whereas 13 and 33 genes were downregulated (≤ 0.67-fold) accompanied by demethylation of CpG islands in male and female offspring mice, respectively. Gene Set Enrichment Analysis (GSEA) revealed that these genes were enriched in gene ontology terms related to the regulation of transcription factors, cell proliferation, and organism development. Additionally, MeSH terms related to stem cells and morphogenesis were enriched. Conclusion: Prenatal TiO2-NP exposure induced genome-wide alterations in DNA methylation and mRNA expression in the brains of male and female offspring. Based on GSEA findings, it can be speculated that prenatal TiO2-NP exposure causes adverse effects on brain functions by altering the DNA methylation state of the fetal brain, especially neural stem cells, resulting in the subsequent abnormal regulation of transcription factors that modulate development and differentiation.